Antipsychotic drugs attenuate aberrant DNA methylation of DTNBP1 (dysbindin) promoter in saliva and post‐mortem brain of patients with schizophrenia and Psychotic bipolar disorder. Issue 8 (18th August 2015) - Abdolmaleky, Hamid M.; Pajouhanfar, Sara; Faghankhani, Masoomeh; Joghataei, Mohammad Taghi; Mostafavi, Ashraf; Thiagalingam, Sam
Abstract : Due to the lack of genetic association between individual genes and schizophrenia (SCZ) pathogenesis, the current consensus is to consider both genetic and epigenetic alterations. Here, we report the examination of DNA methylation status of DTNBP1 promoter region, one of the most credible candidate genes affected in SCZ, assayed in saliva and post‐mortem brain samples. The Illumina DNA methylation profiling and bisulfite sequencing of representative samples were used to identify methylation status of the DTNBP1 promoter region. Quantitative methylation specific PCR (qMSP) was employed to assess methylation of DTNBP1 promoter CpGs flanking a SP1 binding site in the saliva of SCZ patients, their first‐degree relatives and control subjects (30, 15, and 30/group, respectively) as well as in post‐mortem brains of patients with SCZ and bipolar disorder (BD) versus controls (35/group). qRT‐PCR was used to assess DTNBP1 expression. We found DNA hypermethylation of DTNBP1 promoter in the saliva of SCZ patients (∼12.5%, P  = 0.036), particularly in drug‐naïve patients (∼20%, P  = 0.011), and a trend toward hypermethylation in their first‐degree relatives ( P  = 0.085) versus controls. Analysis of post‐mortem brain samples revealed an inverse correlation between DTNBP1 methylation and expression, and normalization of this epigenetic change by classic antipsychotic drugs. Additionally, BD patients with psychotic depression exhibited higher degree of methylation versus other BD patients (∼80%, P  = 0.025). DTNBP1 promoter DNA methylation may become a key element in a panel of biomarkers for diagnosis, prevention, or therapy in SCZ and at risk individuals pending confirmatory studies with larger sample sizes to attain a higher degree of significance. © 2015 Wiley Periodicals, Inc.